ANALYSIS OF PUBLIC HEALTH POLICY IN REDUCING MATERNAL MORTALITY NUMBER - Retnayu Prasetyanti (The Indonesian Journal of Public Administration (IJPA), 2016)
By the emergence of good local governance paradigm,local government must innovatively manage localuniqueness to create community self-reliance in healthcare. By using qualitative perspective and theoreticalanalysis on public policy and sustainable development inlocal context, the research results revealed somedevelopment strategies on health and maternal care.Firstly, (a) upholding cross-sector policies through PublicPrivate Partnership and Good Corporate Governance toserve equitable health outcomes by developing healthinfrastructure and health personnel in local area. (b)Implementing Good Village Governance to enhance localeconomic growth and achieve the outcomes of villageautonomy system. (c) Understanding health as a system,thus, solutions and policy alternatives must considerthinking sub-systems of health care for women, such asgender development and social capital.Keywords: Public Policy, Public Health, Local Wisdom,Development